Contributions of Higher Education to National Security and Counterterrorism in Indonesia - Sulaiman, Sulaiman (Indonesian Journal of Counter Terrorism and National Security, 2024)
This paper explores the significant role that higher education plays in bolstering national security and counterterrorism efforts within Indonesia. It investigates how universities and academic institutions contribute to the development of strategies, policies, and professionals aimed at safeguarding the nation against security threats. By examining the educational, research, and outreach initiatives undertaken by academia, this study aims to elucidate the multifaceted contributions of higher education to Indonesia's security landscape. Using a mixed-methods approach comprising literature review, case studies, and interviews with key stakeholders, the paper examines the diverse ways in which higher education institutions support national security and counterterrorism. It delves into the training and education of security professionals, the research conducted to inform policy decisions, and the engagement with communities to foster resilience against extremist ideologies. Key themes explored include the role of academic curricula in addressing security challenges, the collaboration between universities and government agencies in intelligence and strategic planning, and the promotion of interdisciplinary approaches to understanding and combating terrorism. Additionally, the paper investigates the role of international partnerships and exchanges in enhancing Indonesia's capacity to address security threats. By synthesizing empirical evidence and stakeholder perspectives, this paper aims to provide insights into how higher education can serve as a catalyst for effective national security and counterterrorism measures in Indonesia. It concludes with recommendations for policymakers, educators, and practitioners to further leverage the potential of academia in advancing Indonesia's security agenda.